2020
DOI: 10.1177/0885066620980384
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Personnel Safety During Percutaneous Tracheostomy in Patients With COVID-19: Proof-of-Concept Study

Abstract: Background: Covid-19 pandemic has resulted in the development of severe and persistent respiratory failure requiring long term ventilatory support. This necessitates the need for a reliable and easy to implement tracheostomy protocol given the concern for viral transmission risk to the involved healthcare personnel due to the aerosol generating nature of the procedure. We describe a protocol with unique and novel modifications to the Ciaglia dilatational percutaneous tracheostomy, effectively implemented durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…All procedures were done using PDT with our previously described technique. 11 The mean age was 59 standard deviation (SD = 16) years, 22 (59%) were male, and mean body mass index was 32 (SD = 7.4) ( Table 1 ). The mean APACHE II score at the time of ICU admission was 19 (SD = 8.7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All procedures were done using PDT with our previously described technique. 11 The mean age was 59 standard deviation (SD = 16) years, 22 (59%) were male, and mean body mass index was 32 (SD = 7.4) ( Table 1 ). The mean APACHE II score at the time of ICU admission was 19 (SD = 8.7).…”
Section: Resultsmentioning
confidence: 99%
“…No staff was allowed inside the room for at least one-hour post procedure unless absolutely required. 11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meyer et al reported bronchoscope guided PDT decreased the risk of bleeding in comparison to open tracheostomies, considering the high rate of anti-coagulation therapy required for these patients. Guided PDT reduced transmission of virus to HCWs from critically ill COVID-19 patients [15, 68-69], although there was no major difference in complication rate in PDT compared to open tracheostomy [64, 61]. However, in a pre-COVID study demonstrated that use of bronchoscopes did not affect the overall outcome in patients with open or percutaneous tracheostomy [70].…”
Section: Discussionmentioning
confidence: 99%
“…7 The question of which type of tracheostomy (percutaneous or open tracheostomy) is safer for staff remains controversial. 5,8…”
mentioning
confidence: 99%